Analisis Perbandingan Efektifitas Pupuk Kimia dan Pupuk Organik Terhadap Pertumbuhan dan Produktivitas Tanaman Cabai - Nisiyari Halawa; Florentina Agusmawati Duha; Awal Sepkurniawan Waruwu; Lentri Priskila Waruwu; Arianto Laoli; Benediktus Buala'aro Giawa; Asdian Juliyanti Lawolo; Helmin Parida Zebua (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Fertilizer is an important factor in increasing the growth and yield of chili plants (Capsicum annuum L.). The selection of the right type of fertilizer greatly determines productivity and environmental sustainability in the long term. This study aims to analyze the differences between chemical fertilizers and organic fertilizers in chili plant cultivation, including plant growth, yields, and their impact on soil fertility. The method used is a literature review by examining various previous studies that discuss the effectiveness of both types of fertilizers. The results of the analysis show that chemical fertilizers provide faster growth and higher yields in the short term because their nutrients are more easily absorbed by plants. However, excessive use can cause soil degradation, decreased organic matter content, and environmental pollution. In contrast, organic fertilizers work more slowly, but are able to increase soil fertility, improve soil structure, and support the balance of agricultural ecosystems in the long term. The combination of chemical and organic fertilizers has proven to be the best strategy in increasing chili productivity while maintaining soil health. Therefore, balanced fertilization with the right dose is highly recommended to ensure optimal harvest results without damaging the environment.